BUTAPAS: Inovasi Media Pembelajaran Kontekstual Budaya Palembang Pada Materi Keberagaman Budaya Indonesia di Sekolah Dasar - Wiwin Ulnisah; Tika Dwi Nopriyanti; Laili Rosita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science is one of the independent curriculum learning in elementary school. The science learning process in grade IV of SD Negeri 1 Kaliberau found several problems. Based on the results of observations made that teachers have not used science learning media. The definition aims to develop valid and practical BUTAPAS learning media in grade IV. Calculating using the ADDIE learning model (Analysis, Design, Development, Implementation and Evaluation). So that the results of the bitterness study were obtained with an average score of 98% media experts 100% language experts and 99% material experts have the criteria